PERBANDINGAN KUALITAS HIDUP DAN ACTIVITY OF DAILY LIVING (ADL) PADA PASIEN DENGAN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSUD PASAR MINGGU - Shyawmi Irdianti, (2023)
Stroke is one of the health problems in the world that can be divided into two types, ischemic stroke and hemorrhagic stroke. Ischemic stroke and hemorrhagic stroke can cause symptoms or impacts such as paralysis, visual impairment and impaired cognitive function and memory. The presence of these symptoms and impacts can affect the patient's quality of life. The level of quality of life can also affect daily activities or Activity of Daily Living (ADL). This decrease in ADL occurs due to impaired motor function of stroke patients. This study aims to determine differences in quality of life and Activity of Daily Living (ADL) in patients with ischemic stroke and hemorrhagic stroke at Pasar Minggu Hospital. This study is a quantitative study with a cross sectional approach conducted on 62 respondents with consecutive sampling method. Data were collected using the Stroke Specific Quality of Life (SSQOL) questionnaire to measure quality of life and the Barthel Index (BI) to measure ADL. The results of this study with the Independent T-Test and Mann Whitney test showed that there was a difference between the quality of life of ischemic stroke respondents and the quality of life of hemorrhagic stroke with a p-value of 0.000 (p <0.05) and there was also a difference between ADL of ischemic stroke respondents and ADL of hemorrhagic stroke with a p-value of 0.006 (p <0.05).